Implementing Restorative Justice for Juvenile Offenders of Assault through Progressive Legal Theory within the Women and Children Protection Unit (PPA) of Bone Bolango Police - Sri Afriyanti Botutihe; Darmawati; Sumiyati B (LPPM Universitas Harapan Bangsa, 2026)
The involvement of children as perpetrators of assault poses a significant challenge within the criminal justice system, particularly in fulfilling children's rights and applying restorative justice principles. This study aims to analyze the implementation of restorative justice in fulfilling the rights of child offenders in Bone Bolango Regency, based on the perspective of progressive legal theory. This research uses an empirical legal method with a qualitative approach. Data were collected through in-depth interviews, direct observation, documentation, and literature study, then analyzed descriptively and qualitatively. The findings reveal that the diversion process conducted by the Women and Children Service Unit (PPA) of the Bone Bolango Police has not been implemented optimally. The low success rate of diversion is influenced by the limited participation of victims, inadequate public understanding of restorative justice, and the minimal involvement of legal aid providers and social workers. From the perspective of progressive law, this condition reflects a gap between legal norms and their implementation, indicating that the law has yet to function fully as a means of protection and recovery focused on the best interests of the child. A shift in legal enforcement paradigms is therefore necessary, supported by cross-sectoral collaboration, public education, and strengthened roles of local governments and facilitators in the juvenile justice system.